Measurements of biochemical markers of pollution in mussels Mytilus galloprovincialis from coastal areas of the Saronikos Gulf (Greece) - TSANGARIS, C.; STROGYLOUDI, E.; PAPATHANASSIOU, E. (Mediterranean Marine Science, 2004)
Alterations in a number of biochemical parameters in marine organisms represent specific markers of exposure to particular classes of contaminants. They are used as tools for the detection and monitoring of pollution. In this study, two biochemical markers of pollution, metallothionein (MT) content and acetylcholinesterase (AChE) activity were measured in indigenous and transplanted mussels Mytilus galloprovincialis from coastal areas within the Saronikos Gulf subject to high anthropogenic activities. Biannual measurements of the two biomarkers in indigenous mussel populations for two years revealed no significant differences among stations representing a pollution gradient. Limited differences in MT levels were only found between mussel populations transplanted at lesser and more impacted stations. Both biomarkers showed a variation with respect to the season of sampling, whilst during the second year of measurements a concomitant increase in metallothionein content with a decrease in acetylcholinesterase activity was noted. Our results indicate that the applied biochemical markers in indigenous mussel populations do not reflect the type of pollution in the Saronikos Gulf to a degree that can be used for pollution monitoring in the area.